IMPLEMENTASI PENDIDIKAN RAMAH ANAK DI MADRASAH IBTIDA’IYAH TARBIYATUL ULUM KOTA BATU - Baiq Wahdaniyah; Anwar Sa’dullah; Khoirul Asfiyak (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Education is all activites or conscious offorts made by education to student on all aspects of personality development. Both physical and spiritual, every students has their respective rights both the right to education and the right to protect themselves from various froms of violence because every student has the right to knowledge without any discrimination or violence, the phenomenon of violence in children makes Mi Tarbiyatul UlumKota Batu, make offorts to evercome it through child friendly education programs and always to implement child friendly education in the school enviroment.